Synthesis of Pillar[6]arenes and Their Host–Guest Complexes - Cao, Derong; Meier, Herbert (Synthesis, 2015)
Pillar[n]arenes are a fast-growing research topic in supramolecular chemistry. Originally the focus was predominantly on pillar[5]arenes; however, now more and more studies on pillar[6]arenes are being performed. The ability and selectivity of host–guest complexations depend strongly on the size of the inner cavities of these macrocycles. New results have stimulated us to compile the synthetic entries and the complexations of pillar[6]arenes with large cylindric cavities that offer space for many different guest molecules.1 Introduction2 Preparation of Pillar[6]arenes2.1 Pillar[6]arenes by Macrocyclization Reactions2.2 Hydroxypillar[6]arenes through Ether Cleavage2.3 Hydroxypillar[6]arenes by Redox Reactions2.4 Alkylation of Hydroxypillar[6]arenes2.5 Pillar[6]arenes Obtained from Preformed Pillar[6]arenes by Transformation of Alkoxy Chains3 Structure of Pillar[6]arenes in the Crystalline State and in Solution3.1 Dodecaalkoxypillar[6]arenes3.2 Perhydroxypillar[6]arenes4 Generation of Complexes4.1 Inclusion of Guest Molecules4.2 Complexes of Ammonium Compounds4.3 Complexes of Pyridinium Compounds4.4 Complexes of Other Cations4.5 Complexes of Electroneutral Guest Molecules4.6 Complexes of Anions4.7 Self-Assembly by Complexation4.8 Binding on Metal Surfaces4.9 Capture of Gases and Vapors5 Conclusion
Keywords: condensation; macrocycles; supramolecular chemistry; host–guest systems; arene complexes